Age discrimination causes Unemployment: Evidence from the “35-year-Old phenomenon” in China - Wenlian Lin (China Economic Quarterly International)
Age discrimination in the labor market is a global issue, and in China, it becomes a pressing concern, particularly in the context of so-called “35-year-old crisis.” Departing from the literature that largely relies on resume experiments to identify age discrimination during hiring, I focus on China's labor market and use the 2015 census data to construct a regression discontinuity design for identifying age discrimination and its causal impact on unemployment. The results show that dismissal rates rise significantly immediately after workers exceed the age of 35, even after controlling for productivity-related factors. This rise is driven by negative age stereotypes held by employers and anchoring biases in their employment decisions, but with notable variations across regions, individuals, and time periods.